Microcredit program administered by governmennt agencies in Bangladesh: an assessment and comparison with NGOs programs - Baki, Abdul (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.